CONGENITAL POSTERIOR POLAR CHORIORETINAL HYPOPLASIA: Expansion of the Clinical Spectrum, Mutation, and Its Association With PRDM13. Issue 12 (December 2022) - Small, Kent W.; Tawfik, Caroline A.; Udar, Nitin; Udar, Uma; Avetisjan, Jessica; El-aidy, Lamia A.; Shaya, Fadi S.
Abstract : We describe the clinical and genetic findings of PRDM13-related disorder in an Egyptian family associated with a heterozygous mutation affecting the PRDM13 gene, giving definition to a new disease, congenital posterior polar chorioretinal hypoplasia. Abstract : Purpose: To describe a new ocular phenotype in a single Egyptian family associated with a heterozygous noncoding mutation in the North Carolina macular dystrophy (NCMD/MCDR1) locus, likely affecting the PRDM13 gene. Methods: A retrospective, clinical chart review of 11 members of a four-generation family. Comprehensive ophthalmic examinations included visual acuity, refraction, fundus imaging, spectral-domain optical coherence tomography, and full-field electroretinography. Molecular genetic analysis of the MCDR1 region was performed using whole genome and targeted sequencing. The main outcome measures were DNA sequence variants, clinical, retinal imaging, and electroretinography findings. Results: The five affected adult family members tested carried a single heterozygous mutation in a noncoding region (Chr6:100, 046, 783A>C) located 7.8 kb upstream of PRDM13. Visual acuity ranged from 20/200 to 20/400. All members had extensive chorioretinal absence/thinning extending outside of the maculae with extensive posterior bowing of the choroid and sclera centered in the macula giving a large macular coloboma-like appearance. Two additional members had cystoid fluid, and one had macular detachment. Full-field electroretinography revealed reduced cone and rod responses in all affected members. Conclusion: The phenotype of this disease falls between the spectrum of progressive bifocal chorioretinal atrophy and NCMD. The findings are most consistent with progressive bifocal chorioretinal atrophy with the exception that there is no bifocal nature to the appearance nor is it progressive. Another view is that the phenotype seems to be an extremely severe form of NCMD. Given that this disease falls in between progressive bifocal chorioretinal atrophy and NCMD, we propose calling it congenital posterior polar chorioretinal hypoplasia.